Analisis Tingkat Kepuasan Pengguna terhadap Sistem Absensi Manual di PT. Gracia Jaya Makmur Menggunakan Metode End User Computing Satisfaction - Fresh Krist Wit Nesty Sarumaha; Agus Budiyantara; Sandri Sagitarius Sarumaha (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The advancement of inFormation technology has encouraged many companies to switch to digital attendance systems to improve efficiency and Accuracy in employee attendance recording. However, PT. Gracia Jaya Makmur still uses a manual attendance system that relies on physical records through books or forms. This system is prone to recording errors, time-consuming recap processes, and lacks real-time attendance monitoring. This study aims to analyze user satisfaction with the manual attendance system at PT. Gracia Jaya Makmur using the End User Computing Satisfaction (EUCS) method, which consists of five main dimensions: Content, Accuracy, Format, Timeliness, and Ease of Use. This research employs a descriptive quantitative approach through surveys involving 24 employees as respondents. The results show that the average satisfaction scores across all EUCS dimensions range from 1.83 to 2.02, which fall into the “Poor” category. These findings indicate that the current manual attendance system fails to meet user expectations and requires evaluation and development toward a more effective and efficient technology-based system. This study provides practical contributions for the management of PT. Gracia Jaya Makmur to consider transitioning to a digital attendance system to enhance user satisfaction as well as work effectiveness and productivity.